Whole-genome analysis of temporal gene expression during early transdifferentiation of human lung alveolar epithelial type 2 cells in vitro. - Helena Morales Johansson; Donna R Newman; Philip L Sannes (PLoS ONE)
It is generally accepted that the surfactant-producing pulmonary alveolar epithelial type II (AT2) cell acts as the progenitor of the type I (AT1) cell, but the regulatory mechanisms involved in this relationship remain the subject of active investigation. While previous studies have established a number of specific markers that are expressed during transdifferentiation from AT2 to AT1 cells, we hypothesized that additional, previously unrecognized, signaling pathways and relevant cellular functions are transcriptionally regulated at early stages of AT2 transition. In this study, a discovery-based gene expression profile analysis was undertaken of freshly isolated human AT2 (hAT2) cells grown on extracellular matrix (ECM) substrata known to either support (type I collagen) or retard (Matrigel) the early transdifferentiation process into hAT1-like cells over the first three days. Cell type-specific expression patterns analyzed by Illumina Human HT-12 BeadChip yielded over 300 genes that were up- or down-regulated. Candidate genes significantly induced or down-regulated during hAT2 transition to hAT1-like cells compared to non-transitioning hAT2 cells were identified. Major functional groups were also recognized, including those of signaling and cytoskeletal proteins as well as genes of unknown function. Expression of established signatures of hAT2 and hAT1 cells, such as surfactant proteins, caveolin-1, and channels and transporters, was confirmed. Selected novel genes further validated by qRT-PCR, protein expression analysis, and/or cellular localization included SPOCK2, PLEKHO1, SPRED1, RAB11FIP1, PTRF/CAVIN-1 and RAP1GAP. These results further demonstrate the utility of genome-wide analysis to identify relevant, novel cell type-specific signatures of early ECM-regulated alveolar epithelial transdifferentiation processes in vitro.